Consequences of the Mechanical Action of Excessive Adipose Tissue on the Neighboring Anatomical Structures - Sido, Francisc Grigorescu; Muntean, Valentin; Zimmermann, Anca (Medicine and Pharmacy Reports, 2014)
Obesity is characterized by excess adipose tissue and exerts many negative effects on the health status: increased mechanical pressure on the bone, muscle and joints, distention of the abdominal wall, expansion of the thoracic base, endocrine, cardiovascular and homeostatic dysfunctions etc. There are very scarce data in the literature regarding the mechanical effects of excess adipose tissue on the neighboring anatomical structures. The anatomical alterations of the anterior part of the diaphragm, due to the preperitoneal fat accumulation around the preperitoneal vessels and the biological modulation of the iliac muscle fascia due to mechanical pressure from retroperitoneal fat are only two examples of such an interaction between fat tissue and neighboring anatomical structures. The relationship between preperitoneal fat and anterior part of the diaphragm, analyzed according to age and nutritional status contributes to the understanding of the formation of anterior diaphragmatic arcades, of structural anterior part of the diaphragm alterations and explain the occurrence of acquired non-traumatic anterior diaphragmatic hernias, which are entities not well defined in the literature until now. The consecutive steps in the generation of anterior diaphragmatic hernia could be: accumulation of preperitoneal fat around preperitoneal blood vessels; repeated mechanical pressure on anterior part of the diaphragm, caused by movements, digestive repletion, respiration; induction of anterior arcade formation and fat extension in the mediastinum; progressive enlargement of communication corridors with the mediastinum; weight variations (e.g. rapid weight loss) and passage opening; involvement of the greater omentum and finally the transverse colon on which the greater omentum is inserted. There is no anatomic direct communication between the preperitoneal and the mediastinal fat, the two compartments are separated by a depressed and atrophied zone of the anterior part of the diaphragm.